Digital Image Security Analysis using Hill Cipher and AES Algorithm - Ranti, Dwi; Achmad Fauzi; Sitompul, Melda Pita Uli (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
In today's digital era, digital image exchange has become very common in various industries, but this also increases security risks such as counterfeiting, image manipulation, and information theft. To protect the confidentiality of information in digital images, encryption is a fairly effective method. Hill Cipher, as a classic cryptographic method, offers matrix-based encryption, while Advanced Encryption Standard (AES) is known for its high level of security and efficiency. By combining Hill Cipher and AES, encryption systems can leverage the strengths of classic and modern cryptography together, providing an additional layer of protection that strengthens the security of digital data and reduces vulnerabilities that may exist in each method separately. This approach provides a more comprehensive solution for maintaining the confidentiality of digital images in the context of evolving security threats.